PENGOLAHAN AIR BUNGAN LIMBAH LAUNDRY MENGGUNAKAN BOTTOM ASH SEBAGAI MEDIA ADSORPSI - Fadarina; Indah Purnama Sari; Hafizh Rasi Harahap (Politeknik Negeri Sriwijaya, 2021)
The development of the laundry industry needs attention because generally laundry industry players dispose of waste directly into receiving waters, which causes the water environment to become polluted. Therefore, it is necessary to conduct research to reduce levels of pollutants (BOD, COD, pH, and phosphate). One of the processing techniques that can be used to treat laundry wastewater is the adsorption process. Adsorption occurs because of the attractive forces between the adsorbate molecules on the adsorbent surface. In this study, bottom ash was used as an adsorbent to absorb pollutant levels from laundry waste. This study aims to determine the quality of the absorption of bottom ash adsorbent on the reduction of pollutant levels from laundry waste and the effectiveness of reducing pH, phosphate, COD and BOD levels on variations in the time and weight of the adsorbent used. This laundry waste treatment goes through several stages such as raw material preparation, initial analysis, absorption of laundry waste using bottom ash and final analysis. The results showed that the values of COD, BOD, pH and phosphate after absorption were obtained values of 354.8 mg / L, 129.2 mg / L, 7 and 0.095 mg / L, respectively.